Evaluation of the Moisture Change Ability of Selected Crop Seeds (Agricultural Engineering, 2017)
The objective of the paper was to investigate the moisture change ability of bean, broad bean, pea, lupine, radish, beetroot, winter wheat, maize, cucumber, pumpkin and sunflower seeds. Seeds absorbed water in the system for measurement of the water absorption kinetics with the capillary and weighting method. The research results were presented in the form of plots of the relation of kinetics of the moisture change of seeds in the time for the first and second stage of the process which precedes germination. Moreover, the water content in seeds for the time of the end of the second stage of water absorption was determined and the maximum water absorption speed coefficient and the time of its obtaining was calculated. The water content for the end of the 2nd stage of its collection was the highest for seeds which include a hard caryopsis and for broad bean plant seeds. The maximum water absorption speed coefficient was the highest for seeds with low initial moisture - radish, beetroot, cucumber and pumpkin. The measurement of the water absorption speed with the use of the capillary and weighting method enabled investigation of seeds with a varied size, construction of a seed coat and chemical composition for a long period of time to the moment seedlings were obtained.